Visualization and data analysis 2010 / 18-19 January 2010, San Jose, California, United States - Park, Jinah; IS&T--The Society for Imaging Science and Technology; SPIE (Society); Hewlett-Packard Company (Virgina, US : SPIE, 2010)
PSZJBL